Hiding in Plain Sight - Vijeta Venkataraman; Trudy Rudge; Jane Currie (York University Libraries, 2021)
The incidence of Intimate Partner Violence (IPV) in Australia is rising. Women experiencing IPV seek assistance through Emergency Departments (ED). Women exhibit help-seeking behaviours to nurses who work in emergency over medical or allied health professionals. Nurses' capacity to recognise the need to care for women experiencing IPV is essential. The aim of this study was to explore nurses' capacity to care for women who have experienced IPV through outlining inhibiting factors that limit care and create a discourse that contributes to addressing these factors. Pre (n=10) and post (n=6) focus groups (FGs) were undertaken with nurses who work in ED. In between the FGs an intervention was applied to prompt change to caring practices. The discourse generated from the FGs was subjected to a Foucauldian discourse analysis from a poststructural feminist perspective. Participants' capacity to care was found to be based on the values they formed on IPV, as shaped by their post-registration training. The formation of boundaries was fundamental in inhibiting the participants' capacity to care. Challenging boundaries through educational inquiry into nursing values can be effective in shifting perspectives of IPV. The raising of awareness of IPV in our communities serves as a vital tool in eliciting cultural behaviour change within EDs and within nursing culture.